2013
DOI: 10.1016/j.celrep.2013.11.029
|View full text |Cite
|
Sign up to set email alerts
|

USP10 Antagonizes c-Myc Transcriptional Activation through SIRT6 Stabilization to Suppress Tumor Formation

Abstract: The reduced protein expression of SIRT6 tumor suppressor is involved in tumorigenesis. The molecular mechanisms underlying SIRT6 protein downregulation in human cancers remain unknown. Using a proteomic approach, we have identified the ubiquitin-specific peptidase USP10, another tumor suppressor, as one of the SIRT6-interacting proteins. USP10 suppresses SIRT6 ubiquitination to protect SIRT6 from proteasomal degradation. USP10 antagonizes the transcriptional activity of the c-Myc oncogene through SIRT6, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
137
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(140 citation statements)
references
References 37 publications
3
137
0
Order By: Relevance
“…Moreover, USP10 could stabilize Beclin1 by inhibiting its ubiquitination, which reciprocally stabilizes USP10 and promotes p53-dependent apoptosis (46). A recent report found that USP10 could interact with and deubiquitinates SIRT6, which enhanced SIRT6 stability and resulted in SIRT6/p53-dependent suppression of c-Myc oncogenic activity (47). All of these studies indicate that USP10 may play a tumor-suppressive role by deubiquitinating and stabilizing critical tumor suppressors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, USP10 could stabilize Beclin1 by inhibiting its ubiquitination, which reciprocally stabilizes USP10 and promotes p53-dependent apoptosis (46). A recent report found that USP10 could interact with and deubiquitinates SIRT6, which enhanced SIRT6 stability and resulted in SIRT6/p53-dependent suppression of c-Myc oncogenic activity (47). All of these studies indicate that USP10 may play a tumor-suppressive role by deubiquitinating and stabilizing critical tumor suppressors.…”
Section: Discussionmentioning
confidence: 99%
“…8 In detail, loss of SIRT6 triggers activation of Lin28 promoter, Myc recruitment, and consequent activation of Lin28b, the downstream let-7 target genes (HMGA2, IGF2BP1) and IGF2BP3 that accelerate the PDAC progression and metastasis. 8 In human colon cancer, Lin et al 9 discovered the crosstalk between UPS10 and SIRT6 that regulates cell-cycle progression and proliferation, and showed that the dysregulated USP10 function promotes tumorigenesis through SIRT6 degradation. Lin et al also showed an important reduction in USP10 (a deubiquitinase protein) and SIRT6 expression.…”
Section: Sirt6 As a Tumor Suppressormentioning
confidence: 99%
“…Indeed, the downregulation of USP10 triggers SIRT6 instability and negatively controls the transcriptional activity of the c-Myc oncogene that inhibits cell-cycle progression, cancer cell growth, and tumor formation. 9 In liver cancer, the SIRT6 suppression is regulated by the c-Jun/c-Fos pathway:…”
Section: Sirt6 As a Tumor Suppressormentioning
confidence: 99%
See 1 more Smart Citation
“…SIRT6 is localized in the nucleus [1] and has two types of enzymatic activities: mono-adenosine diphosphate ribosyltransferase [3] and deacetylase [4] activities, both of which are dependent on nicotinamide adenine dinucleotide [5]. SIRT6 regulates various cellular processes, including telomere maintenance, repair of damaged DNA, aging, immunity, and glucose homeostasis, and is important in cancer [3,[6][7][8][9]. SIRT6 deficiency in mice leads to developmental and metabolic abnormalities as well as a shorter lifespan, whereas SIRT6 activation is associated with a longer lifespan [8].…”
Section: Introductionmentioning
confidence: 99%